ERM Report 2009. Restructuring in recession - Hurley, John; Mandl, Irene; Storrie, Donald; Ward, Terry (Luxembourg, 2009)
"Over the course of 2008 and 2009, the world economy experienced one of the most serious recessions in modern times. In July 2009, 22 million men and women were unemployed throughout Europe, five million more than a year previously. Moreover, the situation may well still have further to play out: experience of previous recessions suggests that the full effect of the downturn upon employment has yet to materialise. Eurofound’s analysis of restructuring and job loss over the past year is collated and reviewed in this, the fourth annual report of the European Restructuring Monitor. Analysing the effects of the recession upon employment, it also looks in detail how particular sectors, countries and occupations have been affected, and examines a range of responses that have been taken to safeguard employment - at the company, Member State and European level"